1983
DOI: 10.1172/jci111113
|View full text |Cite
|
Sign up to set email alerts
|

Complementation studies of isovaleric acidemia and glutaric aciduria type II using cultured skin fibroblasts.

Abstract: A B S T R A C T Using cultured skin fibroblasts, we studied the heterogeneity of inborn errors of leucine metabolism such as isovaleric acidemia (IVA), glutaric aciduria type II (GA II), and multiple carboxylase deficiency (MC). We first developed a simple macromolecular-labeling test to measure the ability of cells to oxidize [1-`4C]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…IVDHase activity was found to be uniformly low, regardless of the clinical phenotype (11). We then did genetic complementation studies using polyethylene glycol-induced heterokaryons but failed to demonstrate the existence of genetic heterogeneity (12). However, these results did not exclude the possibility that more than one mutant allele exists, each encoding for a varient IVDHase that is equally deficient in activity.…”
mentioning
confidence: 98%
“…IVDHase activity was found to be uniformly low, regardless of the clinical phenotype (11). We then did genetic complementation studies using polyethylene glycol-induced heterokaryons but failed to demonstrate the existence of genetic heterogeneity (12). However, these results did not exclude the possibility that more than one mutant allele exists, each encoding for a varient IVDHase that is equally deficient in activity.…”
mentioning
confidence: 98%
“…In the previous study of 12 IVA cell lines using polyethylene glycol-induced heterokaryons, no complementation groups were found (14), indicating the involvement of a single IVD gene in this disease. However, the analysis of variant IVD in 15 IVA fibroblast cell lines using [35S]methionine labeling, immunoprecipitation, and SDS-PAGE revealed five distinct classes of variants (10).…”
Section: Introductionmentioning
confidence: 64%
“…The concentration of 3-hydroxyisovaleric acid observed in the control fluids (5.00 + 1.66~tmol/L) is closely comparable to that reported by Jakobs et al (1984) The results of HMG CoA lyase assays of cultured amniocytes confirmed the chemical diagnosis and this was further confirmed by the results of the isovalerate incorporation assay. In the latter assay, the test substrate is introduced at the start of the L-leucine metabolic pathway after ketoacid decarboxylation and thus is suitable for the diagnosis of any enzyme deficiency in the pathway up to entry into the tricarboxylic acid cycle, including isovaleric acidaemia, holocarboxylase synthetase deficiency, 3-methylcrotonylglycinuria and HMG CoA lyase deficiency, and also for multiple acyl CoA dehydrogenase deficiency (Chalmers and Spellacy, 1979;Dubiel et al, 1983;Sovik et al, 1984). The present work indicates the method is also suitable for the prenatal diagnosis of these conditions, offering the potential advantage of a single enzyme assay for the prenatal diagnosis of five different inherited metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%